Relevansi Pemikiran Khas Filsafat Ibn Miskawaih dalam Menjawab Tantangan Zaman - Nurhayati, Fitriani; Hizratul Muttaqien, Qorie; Muttaqin, Via Putrimawati; Santora, Pipih; Hambali, Wisnu; Maulana, Hamdan; Suganda, Ayub; Hermawan, Heris; A. Zein, Irfan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
The moral crisis plaguing modern society requires a philosophical reference that can offer ethical and profound solutions. One important figure in the classical Islamic philosophy who is relevant in this context is Ibn Miskawaih. This research aims to deeply examine Ibn Miskawaih’s ethical thought and its relevance to contemporary moral education. Using the library research method and a descriptive qualitative approach, this study reviews Ibn Miskawaih's main work, Tahdzīb al-Akhlāq wa Taṭhīr al-Aʿrāq, as well as relevant secondary literature. The research results indicate that Ibn Miskawaih's ethical thought emphasizes the integration of Greek philosophical rationality, especially Aristotelianism, with Islamic moral values. He underscores the importance of reason, moral habituation, and the purification of the soul as the foundation for the formation of the ideal human character (insān kāmil). His rational and spiritual approach makes ethics not only a guideline for individuals but also a pillar of harmonious social life. The implications of these findings suggest that Ibn Miskawaih's concept of ethics is still very relevant in shaping sustainable and transformative character education in the modern era